GROWTH OF SALES, INVESTMENT, LIQUIDITY, PROFITABILITY, DAN SIZE OF FIRM TERHADAP KEBIJAKAN DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - -, KHOIRUL HIKMAH; -, RIRIN ASTUTI (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract : This research was to analysis influenced growth of sales, investment, liquidity, profitability, and size of firm to the dividend payout ratio. By using purposive sampling on the data of manufacturing company listed in BEI 2008-2010. The number of sample use in this research were 29 company. Data was analyzed use multiple linier regression. the result of the research indicated that all of variables independent have positive effect together to dividend payout ratio. There was negative effect significant return on equity to DPR, there was no ositive effect significant growth of sale to DPR, there was positive effect significant investment to DPR, there was positive effect not significant liquidity to DPR, there was negative effect not significant profitability to DPR, and there was positive effect not significant size of firm to DPR. Key words: growth of sales, investment, liquidity, profitability, size of firm and dividend payout ratio.